Expressions and stylistic trends of homeowners in terrace housing / Masran Saruwono, Abdurrahman Mohd Rashid and Erdayu Os’hara Omar. - Saruwono, Masran; Mohd Rashid, Abdurrahman; Omar, Erdayu Os’hara (Universiti Teknologi MARA Cawangan Selangor, 2018)
Abstract This study attempts to discover the alteration trends of house renovations focusing on terrace houses. Thirty renovated houses located in Shah Alam were identified, visually observed and analysed. The houses were photographed and sorting process was carried out for analysis at the studio. The results show the altered houses could be classified into four established styles namely; traditional, modern, postmodern and “others”. There is no one particular style of facade that was significantly more popular among them. Something that can be learnt from this study is that people are expressive of their stylistic preferences even under the constraints of the typically narrow-frontaged terrace houses.